Genetic and clinical aspects of paediatric pheochromocytomas and paragangliomas. (28th March 2021) - Petenuci, Janaina; Guimaraes, Augusto G.; Fagundes, Gustavo F.C.; Benedetti, Anna Flavia F.; Afonso, Ana Caroline F.; Pereira, Maria Adelaide A.; Zerbini, Maria Claudia N.; Siqueira, Sheila; Yamauchi, Fernando; Soares, Silvia C.; Srougi, Victor; Tanno, Fabio Y.; et al.
Abstract: Objective: Few and conflicting reports have characterized the genetics of paediatric pheochromocytomas and paragangliomas (PPGLs). This study aimed to investigate the clinical and genetic features of Brazilian children with PPGL. Patients and Methods: This study included 25 children (52% girls) with PPGL. The median age at diagnosis was 15 years (4‐19). The median time of follow‐up was 145 months. The genetic investigation was performed by Sanger DNA sequencing, multiplex ligation‐dependent probe amplification and/or target next‐generation sequencing panel. Results: Of the 25 children with PPGL, 11 (44%), 4 (16%), 2 (8%), 1 (4%) and 7 (28%) had germline VHL pathogenic variants, SDHB, SDHD, RET and negative genetic investigation, respectively. Children with germline VHL missense pathogenic variants were younger than those with SDHB or SDHD genetic defects [median (range), 12 (4‐16) vs . 15.5 (14‐19) years; P  = .027]. Moreover, 10 of 11 cases with VHL pathogenic variants had bilateral pheochromocytoma (six asynchronous and four synchronous). All children with germline SDHB pathogenic variants presented with abdominal paraganglioma (one of them malignant). The two cases with SDHD pathogenic variants presented with head and neck paraganglioma. Among the cases without a genetic diagnosis, 6 and 2 had pheochromocytoma and paraganglioma, respectively. Furthermore, metastatic PPGL was diagnosed in four (16%) of 25 PPGL. Conclusions: Most of the paediatric PPGL were hereditary and multifocal. The majority of the affected genes belong to pseudohypoxic cluster 1, with VHL being the most frequently mutated. Therefore, our findings impact surgical management and surveillance of children with PPGL.